Proceedings of the 3rd International Symposium on Information Processing in Sensor Networks 2004
DOI: 10.1145/984622.984626
|View full text |Cite
|
Sign up to set email alerts
|

Distributed optimization in sensor networks

Abstract: Wireless sensor networks are capable of collecting an enormous amount of data over space and time. Often, the ultimate objective is to derive an estimate of a parameter or function from these data. This paper investigates a general class of distributed algorithms for "in-network" data processing, eliminating the need to transmit raw data to a central point. This can provide significant reductions in the amount of communication and energy required to obtain an accurate estimate. The estimation problems we consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
643
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 783 publications
(644 citation statements)
references
References 12 publications
0
643
1
Order By: Relevance
“…• Remark 5.7 (Discrete-time counterpart of (6) and (11)): It is worth noticing that the discretization of (6) for undirected graphs (performed in [12] for the case of continuously differentiable, strictly convex functions) and (11) for weight-balanced digraphs gives rise to different discretetime optimization algorithms from the ones considered in [1], [2], [3], [4], [5], [6].…”
Section: Lemma 53mentioning
confidence: 99%
“…• Remark 5.7 (Discrete-time counterpart of (6) and (11)): It is worth noticing that the discretization of (6) for undirected graphs (performed in [12] for the case of continuously differentiable, strictly convex functions) and (11) for weight-balanced digraphs gives rise to different discretetime optimization algorithms from the ones considered in [1], [2], [3], [4], [5], [6].…”
Section: Lemma 53mentioning
confidence: 99%
“…The schemes [71,72,73] require specific routing services from the network, e.g. formation and maintenance of cyclic paths that pass through each node in the network.…”
Section: Decentralized Computation In Wireless Sensor Networkmentioning
confidence: 99%
“…Nevertheless, the energy consumption in distributed algorithms may get higher if several iterations are needed to reach a stable estimation of the position [57]. A comparative performance study between distributed and centralized approaches has been presented in [67] and showed that the distributed algorithms are much more efficient, in terms of energy and communication than centralized estimation schemes using both analytical and simulation models. Table 2 summarizes the major differences between distributed and centralized localization approaches.…”
Section: Algorithmsmentioning
confidence: 99%